Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to figure out why $b^n - a^n < (b - a)nb^{n-1}$.

Using just algebra, we can calculate

$ (b - a)(b^{n-1} + b^{n-2}a + \ldots + ba^{n-2} + a^{n-1}) $

$ = (b^n + b^{n-1}a + \ldots + b^{2}a^{n-2} + ba^{n-1}) - (b^{n-1}a + b^{n-2}a^2 + \ldots + ba^{n-1} + a^{n-1}) $

$ = b^n - a^n, $

but why is it necessarily true that $(b - a)(b^{n-1} + b^{n-2}a + \ldots + ba^{n-2} + a^{n-1}) < (b - a)nb^{n-1}$?

Note: I am interested in an answer to that last question, rather than in another way to prove the general inequality in the title...

share|improve this question
1  
For $b>a\ge 0$ it should be obvious, each term is $\le b^{n-1}$. Note things are not quite right, if $b=a$ we do not have $<$. –  André Nicolas Jan 30 '12 at 21:18
    
Not true if e.g. $b=a$. @Andre: Not true if e.g. $b=0>a$ and $n$ is odd. (Edit: nevermind.) –  anon Jan 30 '12 at 21:24
    
Yes, I meant for $0 < a < b$. Sorry! –  jamaicanworm Jan 30 '12 at 22:43

2 Answers 2

up vote 4 down vote accepted

This inequality can fail if $a=b$ or $a$ and $b$ have differing signs: e.g. $b=1$, $a=-3$, and $n=3$. So let's assume that $a\not=b$ and $a,b\ge0$. Division yields $$ \frac{b^n-a^n}{b-a}=\sum_{k=1}^nb^{n-k}a^{k-1}\tag{1} $$ If $a<b$ then obviously, $\sum\limits_{k=1}^nb^{n-k}a^{k-1}=b^{n-1}\sum\limits_{k=1}^n\left(\frac{a}{b}\right)^{k-1}< nb^{n-1}$, thus $\dfrac{b^n-a^n}{b-a}< nb^{n-1}$ and because $b-a>0$, $$ b^n-a^n<(b-a)nb^{n-1}\tag{2} $$ If $a>b$ then obviously, $\sum\limits_{k=1}^nb^{n-k}a^{k-1}=b^{n-1}\sum\limits_{k=1}^n\left(\frac{a}{b}\right)^{k-1}> nb^{n-1}$, thus $\dfrac{b^n-a^n}{b-a}> nb^{n-1}$ and because $b-a<0$, $$ b^n-a^n<(b-a)nb^{n-1}\tag{3} $$ If both $a$ and $b$ are negative, the inequality holds for even $n$, and is reversed for odd $n$.

share|improve this answer

You ask why it is necessarily true that $$(b - a)(b^{n-1} + b^{n-2}a + \ldots + ba^{n-2} + a^{n-1}) < (b - a)nb^{n-1}.$$ A quick answer is that it is not necessarily true. We cannot have strict inequality if $b=a$. And there are other issues. For example, if $n=1$, we always have equality. And the inequality sometimes reverses when one of $a$ or $b$ is negative.

We deal in detail with the cases where $a$ and $b$ are both $\ge 0$. Suppose first that $b>a$, and let $n>1$. Then we want to show that $$b^{n-1} + b^{n-2}a + \ldots + ba^{n-2} + a^{n-1} < nb^{n-1}.$$ The term $b^{n-2}a$ is strictly less than $b^{n-1}$, and there is such a term, since $n>1$. The remaining terms (if any) are also strictly less than $b^{n-1}$. There is a total of $n$ terms, so their sum is strictly less than $nb^{n-1}$.

A similar argument deals with $b<a$. Recall that inequality is reversed when we divide both sides by a negative number. So we want to show that $$b^{n-1} + b^{n-2}a + \ldots + ba^{n-2} + a^{n-1} > nb^{n-1}.$$ Since $b<a$, the term $a^{n-1}$ is strictly bigger than $b^{n-1}$. We don't even need $n>1$. All the other terms are $\ge b^{n-1}$. There is a total of $n$ terms, and the inequality follows.

We stop at this point. The work is incomplete, since we have not dealt with negative numbers. Let $n=3$, $b=0$, and $a=-1$. Then $(b-a)(b^2+ba+a^2)$ is positive, but $(b-a)(3)b^2$ is $0$, so the inequality does not hold. With some work, one can track down all the situations where the inequality does hold.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.